Optimal control strategies for HIV and COVID-19 co-infection: a cost-effectiveness analysis - Batu, Tesfaneh Debele; Obsu, Legesse Lemecha (Frontiers in Applied Mathematics and Statistics, 2024)
In the face of ongoing challenges posed by the COVID-19 and the persistent threat of human immunodeficiency virus (HIV), the emergence of co-infections like COVID-19 and HIV has heightened complexities in disease management. This study aims to identify effective control strategies to mitigate COVID-19 and HIV co-infection, which aggravates the existing challenges posed by these two diseases. To achieve this, we formulated a co-infection model that describes the transmission dynamics of COVID-19 and HIV. Under certain circumstances, we established that HIV infection may facilitate COVID-19 transmission, highlighting the need to identify and implement effective interventions to mitigate COVID-19 and HIV co-infection. As a result, we incorporated four time-dependent control strategies in the co-infection model: HIV prevention, HIV treatment, COVID-19 vaccination, and COVID-19 treatment. Numerical simulations were conducted to support and clarify the analytical results and to show how preventative effortsaffect the co-infected population. Simulations confirm that applying any of the study's strategies will reduce the number of co-infection cases. However, the implementation of these strategies is constrained by limited resources. Therefore, a comprehensive cost-effectiveness analysis was conducted to identify the most economically viable strategy. The analysis concludes that implementing a combined approach of vaccination and treatment for COVID-19 emerges as the most cost-effective measure for preventing the spread of COVID-19 and HIV. These findings provide crucial guidance for decision-makers in adopting precise preventive strategies, ultimately aiming to reduce mortality rates among HIV patients.